2013
DOI: 10.1007/s10549-013-2599-6
|View full text |Cite
|
Sign up to set email alerts
|

Roles of full-length and truncated neurokinin-1 receptors on tumor progression and distant metastasis in human breast cancer

Abstract: Substance P (SP) regulates various physiologic and pathophysiologic responses predominantly by acting through its primary receptor, the neurokinin-1 receptor (NK1R). There are two naturally occurring forms of NK1R: full-length NK1R-FL and truncated NK1R-Tr. SP-coupled NK1R can directly or indirectly regulate the proliferation and metastatic progression of many types of human cancer cells. However, the exact roles played by the two isoforms of NK1R in breast carcinogenesis still remain largely unclear. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 36 publications
4
50
0
Order By: Relevance
“…We have also demonstrated the regulatory effect of NK-1 on prolifer- with Zhou's study [26]. according to previous reports [16][17][18][19][20][21].…”
supporting
confidence: 82%
“…We have also demonstrated the regulatory effect of NK-1 on prolifer- with Zhou's study [26]. according to previous reports [16][17][18][19][20][21].…”
supporting
confidence: 82%
“…In this same sense, one may ask whether the expression of the NK1R receptor, or that of its different splice variants, correlates with the clinical behavior of the tumor and could potentially predict outcome or treatment response. Although somewhat equivocal, evidence from research in breast cancer had previously suggested the existence of such a correlation (41). Our results published in this same special edition of Anticancer Research in primary neuroblastoma cells, in this sense, showed increased gene expression levels of tr-TACR1 and low gene expression levels of fl-TACR1.…”
Section: Therapeutic Innovations In Neuroblastomasupporting
confidence: 53%
“…These findings indicate that targeting Msi1 could be an excellent way to prevent BCC growth. By decreasing TAC1, the level of oncotruncated NK1 could also be negatively regulated (13, 45, 46). This effect would be significant to metastasis, because the TAC1 gene has been linked to bone marrow and brain metastasis (3, 10).…”
Section: Discussionmentioning
confidence: 99%